PENGARUH PRODUKSI DAN TINGKAT PARTISIPASI ANGKATAN KERJA SEKTOR PERTANIAN TERHADAP NILAI TUKAR PETANI DI PROVINSI-PROVINSI INDONESIA PADA MASA PANDEMI COVID 19 - Devi Andriyani; M. Rizky Ananda (Jurnal Ekonomi Pertanian Unimal, 2023)
Research on the Effect of Production and Labor Force Participation (Tpak) in the Agricultural Sector on Farmers' Exchange Rates in 34 Indonesian Provinces During the Covid 19 Pandemic. This study uses secondary data obtained from the Indonesian Central Statistics Agency 2017-2020. This research uses panel data analysis method with the help of Eviews. The results of the study partially show that the production of the agricultural sector has a positive and significant effect on the farmer's exchange rate (NTP), while the labor force participation rate (TPAK) has a positive but not significant effect on the farmer's exchange rate (NTP), and the magnitude of the influence of the production and participation rate variables. The labor force in the provinces in Indonesia to the Farmer's Exchange Rate (NTP) in the provinces in Indonesia is 13.92% while the remaining 86.08% is influenced by other variables outside this research model